Customized logistics service and online shoppers' satisfaction: an empirical study. Issue 2 (4th April 2016) - Hu, Mingyao; Huang, Fang; Hou, Hanping; Chen, Yong; Bulysheva, Larissa
Abstract : Purpose: – Fast-growing online retail market provides convenience for customers. But it makes competition among online retailers fiercer as well. Online retailers need to improve online shoppers' satisfaction level for the purpose of keeping their loyalty. As an important component in online retail market, logistics service affects online shoppers' satisfaction level. By applying expectation confirmation theory, the purpose of this paper is to explore how customized logistics services (CLS) influences online shoppers' satisfaction level and whether the relationship between them is moderated by product type. Design/methodology/approach: – Data were collected fromTmall.com, the biggest online retail market in China. Exploratory factor analysis and two-way ANOVA were conducted to analyze the data. Findings: – The results indicate that CLS positively impacts online shoppers' satisfaction level. But product type does not have moderate effect on the relationship between CLS and online shoppers' satisfaction level. Practical implications: – Online retail market grows fast. As the number of retailers keeps increasing, competition in this market becomes fiercer. In order to attract new shoppers and increase shoppers' loyalty, online retailers must make shopper satisfied with their purchase. CLS positively impacts online shoppers' satisfaction level, online retailers should offer shoppers CLS. Originality/value: – This study examines how customized logistics influences customer satisfaction, and extends literatures related to online customer satisfaction by integrating the factor CLS and opens the way for other studies related to logistics service customization. Furthermore, this study discusses how IoT will improve online retailers' abilities in providing CLS.